2011
DOI: 10.3390/toxins3060520
|View full text |Cite
|
Sign up to set email alerts
|

4-Pyridone-3-carboxamide-1-β-d-ribonucleoside Triphosphate (4PyTP), a Novel NAD+ Metabolite Accumulating in Erythrocytes of Uremic Children: A Biomarker for a Toxic NAD+ Analogue in Other Tissues?

Abstract: We have identified a novel nucleotide, 4-pyridone 3/5-carboxamide ribonucleoside triphosphate (4PyTP), which accumulates in human erythrocytes during renal failure. Using plasma and erythrocyte extracts obtained from children with chronic renal failure we show that the concentration of 4PyTP is increased, as well as other soluble NAD+ metabolites (nicotinamide, N1-methylnicotinamide and 4Py-riboside) and the major nicotinamide metabolite N1-methyl-2-pyridone-5-carboxamide (2PY), with increasing degrees of rena… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 50 publications
0
16
0
Order By: Relevance
“… 23 , 24 4PY is also the substrate for 4-pyridone-3-carboximide-1-β-d-ribonucleoside triphosphate (4PYTP), a novel NAD nucleotide, which has been identified as a biomarker of NAD-induced lymphocyte toxicity in children with renal failure. 56 Another possible inhibitory role of 4PY in PARP1 activity has been described. 24 PARP1 regulates transcription through epigenetic histone modification and transcription factor regulation.…”
Section: Discussionmentioning
confidence: 99%
“… 23 , 24 4PY is also the substrate for 4-pyridone-3-carboximide-1-β-d-ribonucleoside triphosphate (4PYTP), a novel NAD nucleotide, which has been identified as a biomarker of NAD-induced lymphocyte toxicity in children with renal failure. 56 Another possible inhibitory role of 4PY in PARP1 activity has been described. 24 PARP1 regulates transcription through epigenetic histone modification and transcription factor regulation.…”
Section: Discussionmentioning
confidence: 99%
“…The increased incidence of lymphopenia and cancer in CKD patients may be due (at least in part) to (i) lengthy, continuous exposure of the cell’s genome to endogenous DNA-damaging compounds and (ii) hypersensitivity to DNA-damaging agents in general as a result of PARP-1 inhibition. In experiments using a rat model, Synesiou et al found that 4PY accumulation in erythrocytes during kidney failure is a marker for the accumulation of a related toxic NAD+ analogue that inhibits inosine monophosphate dehydrogenase in other cells [31]. Hence, the intra-erythrocyte metabolism of 4PY seems to influence renal anemia—at least in rats.…”
Section: Toxicological Profilementioning
confidence: 99%
“…more or less recently recognised) human metabolites or roles thereof that are worth highlighting, often from studies seeking biomarkers of various diseases – for caveats of biomarker discovery, which is not a topic that we are covering here, and the need for appropriate experimental design, see [201] . Examples include N -acetyltaurine [202] , 27-nor-5β-cholestane-3,7,12,24,25 pentol glucuronide [203] , the cytidine-5-monophosphate:pentadecanoic acid ratio [204] , desmosterol [205] , F 2 -isoprostanes [206–208] , galactose-6-phosphate [209] , globotriaosylsphingosines (lyso-Gb3) [210,211] , cyclic GMP-AMP [212,213] , hexacosanedioic acid [214] , l -homoarginine [94,215,216] , d -2-hydroxyglutarate [217,218] , 3-(4-hydroxy-phenyl)propionic acid [219] , 3-methyl histidine [220] , 3-indoxyl sulphate [221] , N -methyl nicotinamide [188,222] , neopterin [223–225] , ophthalmic acid [226] , O -phosphoethanolamine [227] , 2-piperidinone [228] , pseudouridine [229] , 4-pyridone-3-carboxamide-1-β- d -ribonucleoside triphosphate [230] , Se-methylselenoneine [231] , a mammalian siderophore [232–234] , sphinganine [235] , sphingosine-1-phosphate [236] , succinyltaurine [237] and 3-ureido-propionate [238] , as well as a variety of metabolites coming from or modulated by the human microbiome [100,117,239–244] . Other classes of metabolites not well represented in Recon2 are oxidised molecules [245] such as those caused by nonenzymatic reaction of metabolites with free radicals such as the hydroxyl radical generated by unliganded iron [246–250] .…”
Section: ‘Newly Discovered’ Metabolites And/or Their Rolesmentioning
confidence: 99%